Increasing Learning Achievement of Class IV Students in Social Subject About Nature’s Appearance of Using Interactive Learning Models - Sri Mulyati (Eduvest - Journal of Universal Studies, 2023)
In the teaching and learning process, teachers become the main actors in creating educational interactive situations, namely interactions between teachers and students, students with students and learning resources in supporting the achievement of learning goals. Social studies as one of the fields of study that has the aim of equipping students to develop their reasoning in addition to aspects of values and morals, contains a lot of memorized social material so that the knowledge and information received by students is limited to memorized products. The purpose of this study is to determine the application of learning improvement actions implemented based on the principles of PTK aims as follows: the use of interactive learning models in material about the appearance of nature can improve the learning achievement of grade IV students of SDN Pondok Kacang Timur 03. This research uses qualitative methods with a classroom action research approach. Classroom action research (PTK) is one form of qualitative research. The results showed that from Cycle 1 to Cycle 2 regarding the use of interactive learning models, the author can conclude that; (1) by using interactive learning, it turns out to be able to increase the learning achievement of grade IV students of SD N Pondok Kacang Timur 04 on material about the appearance of nature, and (2) through interactive learning, students can be more active in learning activities, especially in social studies subjects